Determination of Age of Majority In Liability Juvenile Crime in Indonesian Criminal Law - Umar Dinata; Sukamto Satoto; Usman; Erdianto (PT FORMOSA CENDEKIA GLOBAL, 2023)
In juvenile criminal cases, the age limit of children is of great importance, since this obligation to determine whether a suspect belongs to the category of children or not is related to the criminal liability of children. In discussing the extent to which a person can meaningfully be prosecuted as a child, it appears that many laws are inconsistent in their boundaries because they are motivated by the goals of each law. itself. In order to examine the purpose of this study, the purpose of this study is to examine the regulations for determining the age of consent for criminal responsibility of children in the current Indonesian criminal law. This research method uses normative legal research methods, a legal approach, a conceptual approach, a comparative approach and a case approach. The results of this study show that from the minimum age at which children can become important as adults, any legal act of a legal entity can become possible once they reach this legal capacity of adulthood. Aspects of legal protection in determining the age of consent in Indonesian criminal law are related to the criminal liability of children. The measure of a species' ability to assume responsibility can be derived from several factors, ranging from the age to the psychology of the perpetrator. After examining the facts, one can come to the conclusion that the age limit for adulthood, which is pluralism, may lead to ambiguity in determining when a person is declared of adulthood and held responsible for the crimes committed by him becomes